Deval, Juan (2006). Hacia una escuela ciudadana. Madrid: Morata. - Alejandra Navarro Sada (Universidad Autónoma de Madrid, 2018)
Living in an increasingly globalized and diverse world necessarily leads us to question the importance of the limits and possibilities of citizenship education. The recent approval in Spain of the Organic Law of Education (2/2006 of May 3), which establishes among the objectives of primary and secondary education the need to prepare students for the active exercise of citizenship and respect for human rights, has only revived the debate on the advantages and disadvantages of the insertion of a specific subject whose purpose is the training of students in civic and democratic values. The situation in Spain, of course, is not unrelated to what is happening in other places in the world